The molecular mechanism of Gorham syndrome: an update - Xiang, Juqin; Zhong, Weiyang (Frontiers in Immunology, 2023)
Gorham syndrome, also known as "vanishing osteopathy" and "invasive hemangiomatosis", is a rare clinical syndrome whose etiology is unknown and can invade the whole body skeleton. At present, more than 300 cases have been reported at home and abroad, usually manifested as spontaneous chronic osteolysis, with no periosteal reaction at the lysis site and occult onset, often with fractures, scoliosis, chylothorax ,etc. When waiting for medical treatment, the condition is serious and the prognosis is poor. At present, there is no effective treatment. The main pathological manifestations of Gorham syndrome are non-neoplastic abnormal proliferation of lymphatic vessels or blood vessels and osteolysis caused by osteoclast proliferation or increased activity. At present, there is no unified conclusion regarding Gorham syndrome’s pathogenesis. This paper starts with the two most studied osteolysis methods at present, osteoclast osteolysis and osteolysis caused by vascular and lymphatic proliferation, and summarizes the corresponding most possible molecular mechanisms in recent years, to provide more ideas for Gorham syndrome treatment.